La gestión por procesos y sus efectos en el desarrollo de la Empresa Tramacoexpress Cia. Ltda. En la provincia de Chimborazo sucursal Riobamba, periodo 2015-2016. - Naveda Gonzales, Ricardo Paúl (2018)
The present study is about management by processes and their effects in the development of the company Tramacoexpress Cia. Ltda. in the province of Chimborazo with a branch office in Riobamba, term 2015-2016. For the development of the research, information provided directly by the staff was considered, it can be said that management by processes deals with the effective use of resources: economic, human, technological and material in order to meet the objectives and goals in a given period, in addition, the correct use of resources helps to reduce costs, therefore, it allows to offer quality services at a lower cost to meet the expectations of customers. Resource optimization is an excellent technique that must be developed because it is based on efficiency and effectiveness to reach the main objectives with the least amount of effort. It allows the company to synthesize and systematize processes in order to improve the current situation of companies in the market. Finally, through the help of surveys and interviews with internal clients, process management models were considered with the purpose of improving the internal organization and its functions. In addition a guide was developed to optimize resources in an efficient way, which serves as a tool to achieve stablished objectives using the least amount of resources that will improve the business development of the company Tramacoexpress Cia. Ltda.